Predictive Biostatistical Modeling Of Uric Acid Levels Based On High-density Lipoprotein And Alanine Aminotransferase Using R - Wan Muhamad Amir W Ahmad; Mohamad Nasarudin Adnan; Nor Azlida Aleng; Nor Farid Mohd Noor; Ruhaya Hasan; Mohamad Shafiq Mohd Ibrahim; Nurfadhlina Abdul Halim (PUSHPA PUBLISHING HOUSE, 2025)
Indexed Publication (Tier 2)